Algorithm for orchestration of encrypted traffic in SDN networks - Kulakov, Y.O.; Oboznyi, D.M. (Problems of Informatization and Management, 2025)
The article addresses the issue of overload in Software-Defined Networks (SDN) under increasing volumes of encrypted traffic, which complicates its classification and reduces the efficiency of traditional load balancing methods. The proposed algorithm performs preliminary traffic classification using DPI, NBAR, and Cisco AVC technologies, followed by the application of restriction policies for non-priority flows. The solution is based on the M/M/1/K queueing model and considers the characteristics of priority traffic. The proposed approach improves network fault tolerance, enhances the quality of service for critical applications, and reduces data loss in high-load environments.